ANALISA SISTEM PENGELOLAAN SAMPAH DAN PERILAKU PEDAGANG DI PASAR HORAS KOTA PEMATANGSIANTAR TAHUN 2013 - Thomson Siahaan; dr. Surya Dharma MPH; dr. Taufik Ashar MKM (Lingkungan dan Kesehatan Kerja, 2014)
Abstract Analysis the waste management system and trader’s behaviour at Horas Market Pematangsiantar city in 2013.Waste is any materials unused and rejected as worthless or unwanted, useless or profitless activity, expanding and consuming thoughtlessly or carelessly. Subsequent increased of human activitis impact to the increasis of waste. Worse system of waste management will give negative health effects and reduce the quality of urban environment. Therefore it is needed a research to investigate waste management system at Horas Market in Pematangsiantar city. The main purpose of this research is to analoge the waste management system and trader’s behaviour at Horas Market in 2013. The research used descriptive survey method and the population was whole trader’s at Horas Market about 1.219 people with 95 people as sample size. This research used stratified random sampling method by grouping trader’s based on the trader’s group. The resulted of this research showed that most of respondents were female (53,7%), between age of 25-35 years old (36,8%), based on education background were 66,3% senior high school. The waste storage bins at Horas Market is not sufficient. The knowledge level of the respondents in Horas Market in managing waste mostly good category (60,0%). The respondents attitude was mostly manage the waste in good category about 85,3%. The respondents action in managing waste was medium category (76,8%) and good category about 16,8%. Therefore, the government is expected to give more attention and provide the facilities of waste storage bins based on the number of waste generation. Market official is expected to increase the waste transportation and the number of sanitation workers also give the information to the trader’s about a good waste management. All trader’s are expected to provide the storage bins and increase their knowledge,  their attitude and their action about good waste management. Key Words : Waste Management System, Behaviour, Horas Market